The safety and feasibility of laparoscopic right posterior sectionectomy vs. open approach: A systematic review and meta-analysis - Mengxiao, Wang; Linkang, Xiao (Frontiers in Surgery, 2022)
Background Laparoscopic right posterior sectionectomy (LRPS) is one of the most technically challenging and potentially hazardous procedures in laparoscopic liver resection. Although some available literature works demonstrated the safety and feasibility of LRPS, these data are limited to reports from a single institution and a small sample size without support from evidence-based medicine. So, we performed a meta-analysis to assess further the safety and feasibility of LRPS by comparing it with open right posterior sectionectomy (ORPS). Methods MEDLINE, Embase, and Cochrane Library were systematically searched for eligible studies comparing LRPS and open approaches. Random and fixed-effects models were used to calculate outcome measures. Results Four studies involving a total of 541 patients were identified for inclusion: 250 in the LRPS group and 291 in the ORPS group. The postoperative complication and margin were not statistically different between the two groups (OR: 0.49, 95% CI: 0.18 to 1.35, P = 0.17) (MD: 0.05, 95% CI: −0.47 to 0.57, P = 0.86), respectively. LRPS had a significantly longer operative time and shorter hospital stay (MD: 140.32, 95% CI: 16.73 to 263.91, P = 0.03) (MD: −1.64, 95% CI: −2.56 to −0.72, P = 0.0005) respectively. Conclusion Data from currently available literature suggest that LRPS performed by an experienced surgeon is a safe and feasible procedure in selected patients and is associated with a reduction in the hospital stay.